A PROJECT JOURNAL BOOK REVIEW OF JOHN GREEN AND DAVID LEVITHAN’S WILL GRAYSON WILL GRAYSON - Marpaung, Radot Khatrina (LANTERN (Journal on English Language, Culture and Literature), 2017)
There are many kinds of literary works in the world. Then, there are several types of literary works which are novel, drama, short story and poem. They have their own characteristics. Many kinds of literary works can be found easily and have been read by many people as the source of knowledge. Literary works can describe feeling, thinking, and human doing. One of the most interesting literary works that the writer ever read is novel. Novel is one of the literary works in literature that tells narrative story of the characters and their habit which give sense to the readers and also gives strong effect to the readers. “Novel is longer and more complex, requiring a series of sessions for its delivery” (Stevenson,1960:3). It means that, novel tells the story more detail.